2023
DOI: 10.3390/d15091027
|View full text |Cite
|
Sign up to set email alerts
|

Two New Edible Lyophyllum Species from Tibetan Areas, China

Shuhong Li,
Songming Tang,
Jun He
et al.

Abstract: Two new species, Lyophyllum yiqunyang and L. heimogu, that belong to the section Difformia of the genus Lyophyllum, are described based on collections from Tibetan areas, China. The two species are delicious edible low-temperature mushrooms and are widely collected and eaten by local people. Lyophyllum yiqunyang sp. nov. is saprotrophic and has medium-sized basidiomata, olive-grey pileus, cheilocystidia, absent pleurocystidia, globose to subglobose basidiospores (6.12–6.31 × 6.02–6.23 μm) and clamp connections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Among the large fungal resources, Lyophyllum is an important fungal group, but it is difficult to obtain due to its strict growth conditions and the similarity of its pileus color to fallen leaves, which provides them with good camouflage, and this group includes many important edible and medicinal fungi, and the species diversity of Lyophyllum in China is not yet fully understood. Therefore, exploring and protecting China's Lyophyllum resources is significant for maintaining ecological balance and biodiversity (Li S. et al, 2023). In our research, we found that there may be more than 15 potential species of Lyophyllum in China, and more than half of them may be found in Qinghai.…”
Section: Figurementioning
confidence: 69%
“…Among the large fungal resources, Lyophyllum is an important fungal group, but it is difficult to obtain due to its strict growth conditions and the similarity of its pileus color to fallen leaves, which provides them with good camouflage, and this group includes many important edible and medicinal fungi, and the species diversity of Lyophyllum in China is not yet fully understood. Therefore, exploring and protecting China's Lyophyllum resources is significant for maintaining ecological balance and biodiversity (Li S. et al, 2023). In our research, we found that there may be more than 15 potential species of Lyophyllum in China, and more than half of them may be found in Qinghai.…”
Section: Figurementioning
confidence: 69%
“…Larsson and Sundberg [10] provided ITS and LSU data, which provided more evidence for identifying species. Later, several Lyophyllum species were published based on ITS and LSU data [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Among the large fungal resources, Lyophyllum is an important fungal group, but it is difficult to obtain due to its strict growth conditions and the similarity of its pileus color to fallen leaves, which provides them with good camouflage, and this group includes many important edible and medicinal fungi, and the species diversity of Lyophyllum in China is not yet fully understood. Therefore, exploring and protecting China's Lyophyllum resources is significant for maintaining ecological balance and biodiversity (Li S. et al, 2023). In our research, we found that there may be more than 15 potential species of Lyophyllum in China, and more than half of them may be found in Qinghai.…”
Section: Figurementioning
confidence: 69%